Reparations and the Human - Eng, David L. (Columbia Journal of Gender and Law, 2011)
I would like to begin by returning to Antigone’s Claim insofar as it traces a particular strain of thought in Judith Butler’s writings about the relationship between social difference and the problem of the human. Sophocles’s Oedipus trilogy has been subject to a myriad of interpretations in philosophy, classics, literature, and political theory. Butler’s reading of Antigone, the third installment of the Oedipus cycle, is singular, however, insofar as it reconceptualizes conventional understandings of the relations among the incest taboo, kinship, the state, and the possibilities for social change and belonging. If the incest taboo might be reconceived outside of its normative Oedipal resolutions, Butler asks, what new forms of kinship and sociality might emerge outside of conventional heterosexual arrangements to challenge as well as incite state recognition of non-normative sexualities and communities? In the eyes of the law, what today counts as a livable and grievable life today, and what does not? These questions have consequential implications for war, violence, and mourning, as Butler shows us with increasing urgency in her more recent works, and for contemporary legal notions of reparations, the human, and human rights, as I hope to suggest in this article.